"Not in the 1968". The Greek university students rebellion in 1973 and its aftermath in the 2015 Greek multi-crisis - Dimitrios Foteinos (Globalizing the student rebellion in the long ’68, 2018)
In the 1973 November 17 the (Greek) Polytechnic University students did revolt. Comparing to other students’ revolts across Europe and elsewhere this rebellion was delayed due to the military junta outburst in Greece in 1967 (which, apparently, restricted and restrained any political movements). Apart from the literature that either emphasizes on the political and ideological meanings of this uprising or on the negation of it, it seems interesting to search for its imprint in social attitude, given the 2010-2018 Greek multi-crisis and the many riots outburst, whereas the 62% "NO" in the "2015 bailout referendum"can be considered as a milestone of this social attitude and of the crisis as well. This presentation aims to search the connections between (a) the "myth" behind the youth (and people’s) resistance, which can be briefly mentioned as "resistance culture" along with the educational myths that cultivated this culture, and (b) the "anti-...(anything)" movement and the following riots which devastated institutions and cities across Greece, particularly during this period of multi-crisis. An historiographical and genealogical method will be used in order to reveal the roots of the societal attitude towards this "resistance culture". The Press and other Media as well as the school history curriculum could be considered as the historical data to proof these connections. The highly ideologized perception of the past (which includes the "1973 November 17 th " students’ uprising) on behalf of certain political parties (or groups) and the social legitimization of this perception through school is expected to be emerged as a conclusion.